The Norwegian Mother and Child Cohort Study (MoBa) - new research possibilities - Per Magnus (Norsk Forening for Epidemiologi, 2007)
The Norwegian Mother and Child Cohort Study (MoBa) is an observational, prospective study of up to 100 000 families. The study aims to find causes of diseases, with a focus on the interplay between early exposures and genetic factors. The collection of possible exposures starts in pregnancy. As of September 2007, about 80 000 families participate. A series of subprojects are ongoing, and analyses and publications are on their way. This paper presents the present situation of MoBa, and highlights new challenges and opportunities.